Current and Future Aspects of Nanomedicine - Ahmed Hamed Khalil, Islam (IntechOpen, 2020)
Nanomedicine refers to the use of nanotechnological applications in biomedical fields such as therapeutics, diagnostics, monitoring, visualization, tissue engineering and even surgery. This book presents recent updates in the nanomedicine market and discusses several aspects of drug delivery and tissue regeneration using different platforms and devices.